OPTIMASI KECEPATAN MOTOR DC MENGGUNAKAN PID DENGAN TUNING ANT COLONY OPTIMIZATION (ACO) CONTROLLER - Mochammad Nur Masrukhan; Mochamad Piono Mulyo; Dwi Ajiatmo; Machrus Ali (SENTIA 2016, 2016)
Characters of the DC motor is non linear and for the permanent magnet is linear. Non- linear characteristics of DC motors such as friction and saturation can degrade the performance of conventional controls. This can be overcome by intelligent control based Artificial Intelligent (AI). In this study, designed the model of DC motor speed control using multiple controls, which autotuning matlab PID control, PID with tuning Ant Colony Optimization (ACO). The results of the performance of the model DC motor speed control using the PID-ACO found to have a steady state error, settling time and overshoot are better than the PID Autotuning Matlab, PID-ZN (Ziegler Nichols PID). From the results of running the program get that PID-ACO in this study is the best controller with the fastest time settling is 0.55 seconds and overshot the smallest is 1,017.